2022
DOI: 10.1093/molbev/msac268
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of Hard Sweeps on the X Chromosome in Drosophila melanogaster

Abstract: The characteristic properties of the X chromosome, such as male hemizygosity and its unique inheritance pattern, expose it to natural selection in a way that can be different from the autosomes. Here, we investigate the differences in the tempo and mode of adaptation on the X chromosome and autosomes in a population of Drosophila melanogaster. Specifically, we test the hypothesis that due to hemizygosity and a lower effective population size on the X, the relative proportion of hard sweeps, which are expected … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 100 publications
(205 reference statements)
2
16
0
Order By: Relevance
“…A classic question in evolutionary biology is how the evolution of the X chromosome differs from that of autosomes given the X chromosome's central role in speciation, brain function, fertility, and sexual dimorphism (Rice 1984;Saifi and Chandra 1999;Skuse 2005;Dean and Mank 2014;Payseur et al 2018). Past work has suggested that the X chromosome may exhibit different evolutionary dynamics from the autosomes due to its unique inheritance pattern and increased exposure to selection through male hemizygosity (Vicoso and Charlesworth 2006;Nam et al 2015;Charlesworth et al 2018;Muralidhar and Veller 2022;Harris and Garud 2023). Recently, we found evidence in a North American D. melanogaster population that the X chromosome experiences an enrichment of hard selective sweeps compared to autosomes due to the increased visibility of new deleterious mutations to natural selection on the hemizygous X of males and reduced effective population size on the X (Harris and Garud 2023).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A classic question in evolutionary biology is how the evolution of the X chromosome differs from that of autosomes given the X chromosome's central role in speciation, brain function, fertility, and sexual dimorphism (Rice 1984;Saifi and Chandra 1999;Skuse 2005;Dean and Mank 2014;Payseur et al 2018). Past work has suggested that the X chromosome may exhibit different evolutionary dynamics from the autosomes due to its unique inheritance pattern and increased exposure to selection through male hemizygosity (Vicoso and Charlesworth 2006;Nam et al 2015;Charlesworth et al 2018;Muralidhar and Veller 2022;Harris and Garud 2023). Recently, we found evidence in a North American D. melanogaster population that the X chromosome experiences an enrichment of hard selective sweeps compared to autosomes due to the increased visibility of new deleterious mutations to natural selection on the hemizygous X of males and reduced effective population size on the X (Harris and Garud 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Past work has suggested that the X chromosome may exhibit different evolutionary dynamics from the autosomes due to its unique inheritance pattern and increased exposure to selection through male hemizygosity (Vicoso and Charlesworth 2006;Nam et al 2015;Charlesworth et al 2018;Muralidhar and Veller 2022;Harris and Garud 2023). Recently, we found evidence in a North American D. melanogaster population that the X chromosome experiences an enrichment of hard selective sweeps compared to autosomes due to the increased visibility of new deleterious mutations to natural selection on the hemizygous X of males and reduced effective population size on the X (Harris and Garud 2023). However, it is unclear whether this pattern of enrichment of hard sweeps on the X is a universal feature across all heterogametic species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, many studies utilizing genome‐wide scans of selection have recovered signatures of well‐documented selection at genes such as Cyp6g1 , Ace and CHKov1 (e.g. see Duneau et al, 2018; Garud et al, 2021; Harris & Garud, 2023; Kapun et al, 2020). Single‐gene studies are also important in their own right, as they can help us to better understand the myriad of mechanisms through which selection can act as well as the molecular functions and environmental conditions that drive it.…”
Section: Allele Frequency Variation and Dynamics In Natural Drosophil...mentioning
confidence: 99%